Minat Investasi Syariah Generasi Z: TPB, Perilaku Keuangan, dan Religiusitas - Hermita Hermita; Dian Dikawati; Nur Azikin (Jurnal Ilmiah Ekonomi Islam, 2023)
The Islamic capital market industry in Indonesia is experiencing relatively significant growth. However, in comparison to its conventional counterpart, the development of the Islamic capital market in Indonesia is considerably low. The Z-generation is a great potential that is expected to contribute to the improvement of the Islamic capital market. This study aims to examine factors influencing the intention of the younger generation in investing in the Islamic capital market by analyzing and assessing the influence of financial behavior, investment attitudes, subjective norms, perceptions of behavioral control and religiosity factors on intention to invest in the Islamic capital market. This study employs a quantitative approach with multiple linear regression analysis using t-test and f-test. The results show that investment attitudes and subjective norms affect investment willingness of the youth in the Islamic capital market, which means individual beliefs based on self-assessment and those obtained from people around the individual contribute to the intention of the youth to invest in the Islamic capital market. Interestingly, financial behavior, perceived behavioral control, and religiosity have no effect on the younger generation's investment interest in the Islamic capital market.